2017
DOI: 10.2528/pierc17080103
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Design and Testing of a Dielectric Embedded Tapered Slot Uwb Antenna for Breast Cancer Detection

Abstract: Abstract-A distortion-less ultra-wideband tapered slot antenna is designed to achieve wide band impedance matching and high gain without requiring coupling liquids. The antenna is embedded in a suitable dielectric material for compact size and performance improvement. The near-field test is simulated by placing several field probes near the antenna to plot the radiation pattern and polarization isolation. The antenna exhibits a highly directive pattern and polarization isolation in near field. The time domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…In the simulation, the databases in [21] are used to obtain the frequency-dependent skin permittivity and conductivity. The dispersion curves of fat and glandular were calculated according to (25)-(28) below [22,23]. The second-order fitting curve is considered in the calculation for better accuracy…”
Section: Simulation and Resultsmentioning
confidence: 99%
“…In the simulation, the databases in [21] are used to obtain the frequency-dependent skin permittivity and conductivity. The dispersion curves of fat and glandular were calculated according to (25)-(28) below [22,23]. The second-order fitting curve is considered in the calculation for better accuracy…”
Section: Simulation and Resultsmentioning
confidence: 99%
“…16 Because of easy construction and obtainability of material, a prototype of breast mimic manufactured by using unflavored gelatin crystal layer (ε r = 45-65, σ = 5-20 S/m), petroleum jelly as fat (ε r = 2.36, σ = 0.0012 S/m), and wheat flour + water as tumor (ε r = 23, σ = 2.57 S/m) is used. 17 For the validation of simulated S-parameter, the fabricated DRA is connected to the VNA E5063A. A DRA is placed parallel to the experimentally prepared breast mimic at distance of 5 cm.…”
Section: Experimental Validation Of Usage Of the Proposed Dra For Rmentioning
confidence: 99%
“…In order to prove the efficiency of the proposed system in context to the existing literature in this regard, Table 5 compares the performance of the proposed breast cancer detection technique as to the existing techniques reported in the literature. It is observed that the techniques reported in [23, 24, 26] used multistatic radar-based cancer detection (using larger sized antennas except one); therefore the mentioned MWI techniques required the use of an antenna array for the detection and imaging procedure. Secondly, the work reported in [23, 24, 26] did not take into account the SAR of the antennas on the breast phantoms, the frequency band used in the reported work was also poorly matched in terms of impedance bandwidth and some of the researchers did not validate their technique with a breast phantom experimentally.…”
Section: Beam-forming Das Algorithmmentioning
confidence: 99%
“…It is observed that the techniques reported in [23, 24, 26] used multistatic radar-based cancer detection (using larger sized antennas except one); therefore the mentioned MWI techniques required the use of an antenna array for the detection and imaging procedure. Secondly, the work reported in [23, 24, 26] did not take into account the SAR of the antennas on the breast phantoms, the frequency band used in the reported work was also poorly matched in terms of impedance bandwidth and some of the researchers did not validate their technique with a breast phantom experimentally. The work reported in [25] makes use of a MPA with a reduced ground but their proposed antenna was not able to excite the UWB, the tumor diameter was considered as 13 mm in this case.…”
Section: Beam-forming Das Algorithmmentioning
confidence: 99%
See 1 more Smart Citation